FMRP-Driven Neuropathology in Autistic Spectrum Disorder and Alzheimer's disease: A Losing Game - Bleuzé, Louis; Triaca, Viviana; Borreca, Antonella (Frontiers in Molecular Biosciences, 2021)
Fragile X mental retardation protein (FMRP) is an RNA binding protein (RBP) which absence is essentially associated to Fragile X syndrome (FXS). As RNA binding protein, FMRP is able to bind and recognize different RNAs structure and the control of specific mRNAs is important for the neuronal synaptic plasticity. Perturbations of this pathway has been associated to the autistic spectrum. One of the FMRP partner is the APP mRNA, the main protagonist of Alzheimer’s disease (AD), thereby regulating its protein level and metabolism. This molecular link associates FMRP to two neurodevelopmental and age-related degenerative conditions, respectively Fragile X syndrome and AD. Although the extremely different pathologies, they have been reported to share a number of common molecular and cellular players. The aim of this review is to describe the double-edged sword of FMRP in autism and AD, possibly allowing the elucidation of key shared underlying mechanism and neuronal circuits. As RNA binding protein, FMRP is able to regulate APP expression acting on the production of amyloid β fragments. Indeed, FXS Patients show an increase of amyloid β production, typical of other neurological disorders, such as Alzheimer disease, Down syndrome, etc. Beyond APP dysmetabolism, the two pathologies share molecular targets, brain circuits and related cognitive deficits. In this review, we will point out the potential common neuropathological pattern, which needs to be identified and hopefully contribute to clarify the complex phenotype of these two tremendous neurological conditions, in order to pave the way for a novel, shared disease-modifying therapy.